2011
DOI: 10.1089/vbz.2010.0128
|View full text |Cite
|
Sign up to set email alerts
|

The Delicate Pygmy Rice Rat (Oligoryzomys delicatus) Is the Principal Host of Maporal Virus (FamilyBunyaviridae, GenusHantavirus)

Abstract: Choclo virus (CHOV) and Maporal virus (MAPV) are enzootic in Panama and western Venezuela, respectively. The results of previous studies suggested that the fulvous pygmy rice rat (Oligoryzomys fulvescens) is the principal host of both viruses. The results of an analysis of nucleotide sequence data in this study indicated that the rodent associated with CHOV is the Costa Rican pygmy rice rat (Oligoryzomys costaricensis) and that the rodent associated with MAPV is the delicate pygmy rice rat (Oligoryzomys delica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 26 publications
(30 reference statements)
3
58
0
1
Order By: Relevance
“…5 to 10 % [Feijoo et al 2010;D'Elía et al in press]; species of the Akodon boliviensis species group: 2.8-7.7 % [Jayat et al 2010]; Eligmodontia: 4.6-11.4 % [Mares et al 2008]; Juliomys: ca. 12 % ; Melanomys: 4.5-7.6 % [Hanson and Bradley 2008]; Nectomys: 7.36 % [Hanson and Bradley 2008]; Oligoryzomys: 4.45-15 % [Hanson et al 2011;Palma et al 2010;Richter et al 2010;Rogers et al 2009]; Oryzomys: 4.5-12.1 % ; Oxymycterus: 2.5-9.6 % [Jayat et al 2008 [Henson and Bradley 2009]). Although the species used for comparison are not the closest possible relatives to Neusticomys, all belong to other sigmodontine tribes and provide a diverse array of reference points.…”
Section: Discussionmentioning
confidence: 99%
“…5 to 10 % [Feijoo et al 2010;D'Elía et al in press]; species of the Akodon boliviensis species group: 2.8-7.7 % [Jayat et al 2010]; Eligmodontia: 4.6-11.4 % [Mares et al 2008]; Juliomys: ca. 12 % ; Melanomys: 4.5-7.6 % [Hanson and Bradley 2008]; Nectomys: 7.36 % [Hanson and Bradley 2008]; Oligoryzomys: 4.45-15 % [Hanson et al 2011;Palma et al 2010;Richter et al 2010;Rogers et al 2009]; Oryzomys: 4.5-12.1 % ; Oxymycterus: 2.5-9.6 % [Jayat et al 2008 [Henson and Bradley 2009]). Although the species used for comparison are not the closest possible relatives to Neusticomys, all belong to other sigmodontine tribes and provide a diverse array of reference points.…”
Section: Discussionmentioning
confidence: 99%
“…Whenever possible, we selected sequences of individuals from which Hantavirus genotypes were detected. In the cases where the sequence of an infected specimen was not available, we selected a cyt-b sequence of the species analysed in reliable phylogenies (Hanson et al, 2011;González-Ittig et al, 2014). The tree was rooted relative to the position of Peromyscus maniculatus (JF489123) and Neotoma lepida (AF307833).…”
Section: Methodsmentioning
confidence: 99%
“…A study in this direction would be particularly interesting for South American hantaviruses, since the greatest diversity in the western hemisphere lies clearly in this region (Firth et al, 2012). One of the main limitations to understanding the importance of preferential host switching is the disagreement among different studies about the virus-host relationships they assess (see González-Ittig et al, 2014), often as a consequence of poorly resolved taxonomies in some rodent lineages (Almeida et al, 2007;Haag et al, 2007;González-Ittig et al, 2010;Hanson et al, 2011). For example, Maporal and Choclo viruses were detected in specimens originally assigned to Oligoryzomys fulvescens but later Hanson et al (2011) demonstrated that the rodent hosts were Oligoryzomys delicatus and Oligoryzomys costaricensis, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recent phylogenetic studies of this genus (Rivera et al, 2007;Rogers et al, 2009;Miranda et al, 2009;Palma et al, 2010a;González-Ittig et al, 2010Hanson et al, 2011;Agrellos et al, 2012;Teta et al, 2013) have shown that Oligoryzomys systematics is still controversial, probably due to the high phenotypic similarity between species, which makes diagnosis and species identification difficult (see Musser, 1989, 1995;Weksler andBonvicino, 2005, 2015, for historical accounts of the generic taxonomy). In addition, molecular studies not employing morphological examination of specimens hinders further advance of the systematics of the genus, as specific names have been attached to several exemplars without a proper morphological assessment or that are based solely on geographic proximity of species ranges or type localities.…”
Section: Introductionmentioning
confidence: 99%